High bacterial activity in nutrient rich saltwater: Evidence from the uncoupling between salinity and nutrients in the Patos Lagoon estuary. (5th January 2019) - They, Ng Haig; Marins, Luís Fernando; Möller, Osmar Olinto; Abreu, Paulo Cesar
Abstract: In estuaries, a common pattern found is of higher bacterial activity in freshwater than in saltwater, an indication of the existence of an activity gradient. It is not clear, however, whether this arises from a natural property of saltwater bacterial communities or from metabolic constraints imposed from the natural co-variation between salinity and nutrients in estuarine systems. In this study, we managed to detect in situ higher activity levels of free-living bacteria in nutrient-rich saltwater entering the Patos Lagoon estuary. The bacterial community composition (BCC - Temporal Temperature Gradient Gel Electrophoresis) and activity (community-level physiological profiles, CLPP- Ecoplate™ - Biolog) were evaluated during two days in a transect along the estuary until the adjacent coastal region. The unexpected higher nutrient content and bacterial activity in saltwater found suggest that the bacterial activity is a primary response to nutrient availability, whereas salinity is the main factor structuring BCC in this estuary. Our results reject the idea of a natural low activity of saltwater bacteria by showing that their activity can increase in situ given that the proper conditions are met, especially in estuaries that display circulation patterns that promote the occurrence of nutrient-rich saltwater. Graphical abstract: Highlights: Bacterial diversity was structured by salinity. Bacterial activity is structured by nutrients content of the water, regardless the salinity of the samples. In microtidal estuaries such as the Patos Lagoon estuary, marine water intrusion is decoupled from tides, resulting in nutrients and salinity that do not covary.